Detection of Sepsis in Preterm Infants by Fecal Volatile Organic Compounds Analysis: A Proof of Principle Study. Issue 3 (September 2017) - Berkhout, Daniel J.C.; Niemarkt, Hendrik J.; Buijck, Martin; van Weissenbruch, Mirjam M.; Brinkman, Paul; Benninga, Marc A.; van Kaam, Anton H.; Kramer, Boris W.; Andriessen, Peter; de Boer, Nanne K.H.; de Meij, Tim G.J.
ABSTRACT: Objectives: Several studies associated altered gut microbiota composition in preterm infants with late-onset sepsis (LOS), up to days before clinical onset of sepsis. Microbiota analysis as early diagnostic biomarker is, however, in clinical practice currently not feasible because of logistic aspects and high costs. Therefore, we hypothesized that analysis of fecal volatile organic compounds (VOCs) may serve as noninvasive biomarker to predict LOS at a preclinical stage, because VOC reflect the composition and activity of intestinal microbial communities. Methods: In a prospective multicenter study, fecal samples were collected daily from infants with a gestational age of <30 weeks. VOC signatures of fecal samples from infants with LOS, collected up to 5 days before diagnosis, were analyzed by means of an electronic nose technology (Cyranose 320) and compared to matched controls. Results: Fecal VOC profiles of infants with LOS (n = 36) could be discriminated from controls (n = 40) at 3 days (area under the curve [±95% confidence interval], P value, sensitivity, specificity; 70.2 [52.2–88.3], 0.033, 57.1%, 61.5%), 2 days (77.7 [62.7–92.7], 0.050, 75.0%, 70.8%), and 1 day (70.4 [49.6–91.3], 0.037, 64.3%, 64.3%) before the onset of LOS. Conclusions: Fecal VOC profiles of preterm infants with LOS could be discriminated from matched controls, up to 3 days before clinical onset of the disease, underlining the hypothesis that intestinal microbiota may play an etiological role in LOS. Notably, VOC profiling is clinically feasible and the potential of this technique in the early detection of LOS needs to be confirmed in future studies. Abstract : Supplemental Digital Content is available in the text